Pertumbuhan Dan Kecernaan Protein Ikan Lele Dumbo (Clarias gariepinus) yang Diberi Pakan Berbasis Tepung Usus Ayam Sebagai Pengganti Tepung Ikan - Yoel Yoel; Burhanudin Sundu; Fadly Y. Tantu (Mitra Sains, 2016)
The research aims to determine the effect of different feed ingredient as a source of animal protein fed to Dumbo Catfish (Clarias gariepinus). The study was conducted at Tatura Utara village, Palu Selatan sub district, Palu District from January to March 2015. A total of 240 fish seeds were fed with diet containing either fish meal, chicken intestime meal or their combination. Parameters observed were growth of biomass weight, protein digestibility and FCR. Data were analyzed by analisys of variance with completely randomized factorial design. Results indicated that the effect of tipe of animal protein, the quantity of feed offered and their interactions produced significant different in biomass weight, protein digestibility and FCR, except quantity of feed offered did not produced significant different in protein digestibility. Means growth of biomass weight and protein digestibility from each treatment were 5.174 g and 85.9% for chicken intestine meal, 9.6 g and 95.1% for fish meal, 7.9 g and 92.5% for chicken intestine meal + fish meal, and 7.9 g and 91.3% for at satiation and 7.2 g and 7.2 g and 91.0% for 4% biomass treatment and interaction between fish meal and at satiation were 9.6 g and 95.4%. in conclusion, the use of fish meal and the interaction between fish meal and at satiation produced biomass weight and protein digestibility in the highest level in this study.